PENGARUH KONSELING KELOMPOK DENGAN TEKNIK SELF-TALK DALAM MENINGKATKAN ACADEMIC HARDINESS SISWA - Eka Wahyu; Ellita, Yessy; Afriwilda, Mayang T. (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2024)
The research aims to prove the effect of group counseling services using self-talk techniques in increasing students' academic hardiness. The research was conducted using an experimental method with a two group pre-test post-test control design. The population in this study was class XI IPS Negeri 4 Bengkulu city, totaling five classes. The research sample consisted of 10 students including 5 students in the experimental group class XI IPS 1 and 5 students in the control group class XI IPS 4 taken using a purposive sampling technique. The data collection technique uses an academic hardiness questionnaire with a Likert scale model, and research data analysis uses the One Way Anova test. The results of the pre-test and post-test for the experimental group showed an average increase of 57.6 to 104.6. Meanwhile, the pre-test and post-test results of the control group showed an increase in the average score from 69.2 to 78.2. The results of hypothesis testing using the One Way Anova test, F value 33.833 and sig 0.000, show that there is a difference in the level of academic hardiness between students who received group counseling with self-talk techniques and the academic hardiness of students who received group counseling without techniques. So the research results show that there is an influence of group counseling services with self-talk techniques in increasing academic hardiness.